Modelling an adequate profile for a more targeted work methodology, with dedicated technologies, for elite-level footballers: comparison between sub 17 vs sub 19, highlights and shadows - Izzo, R.; Raiola, G.; D`Isanto, T.; Cejudo, A.; Giovannelli, M. (Sport Science - International Scientific Journal of Kinesiology, 2020)
Purpose: The aim of this study is to compare physical performance during official match (under 17 Championship Serie A and B, under 19Serie B) in two different professional football team and analyze which are the physical parameters that differentiates better under 17 (U-17) and under 19 (U-19) young elite-level football teams. Method: Forty-five (n=45) professional soccer players were analyzed (n=23 under 17; age 16.5±0.5 body weight 69.8±7.0 kg; height 177±8.0cm; fat mass 8.2±3.6 %) and (n=22 under 19; age 17±0.4 years, body weight 70.9±5.8 kg; height 180±5.3 cm; fat mass 8.9±3.6%),excluding goalkeepers, they have been analyzed during 50 official matches (2017-2018: 26 Matches U-17 and 24 Matches U-19 respectively) with K-GPS 20Hz (K-Sport Universal STATS, Montelabbate (PU), Italy). Results: Distance covered at very high intensity acceleration (D_A8, m) is significantly higher in U-19 vs U-17 (ES=1.14; p<0.05). Deceleration at very high intensity (D_A1, m) is significantly higher in U-19 vs U-17 (ES=0.70; p<0.05). Instead metabolic power average event (MPA(W/Kg)) is significantly higher in U-17 vs U-19 (ES=1.17; p <0.05). These events are very different in global analysis of season for under 17 and under 19 (first leg + second leg); we found the same situation in first leg period analysis (U-19 vs U-17). The situation changes in the second part of the season where only metabolic power average event (MPA, w/kg) changing significantly in U-17 being larger than U-19 (ES=1.44; p<0.05). In the second part of the season (second leg), other parameters are improved in U-17 and they are close to U-19 external training load. Conclusion: This comparison is important to understand better structural and body differences between two different ages in elite-level young footballers groups. This study confirm that high intensity acceleration (> 3m/s²), are greater in U-19 respect to U-17, in the entire season, in fact this parameter is correlated with the development of strength and muscle mass (growth process).This underline the importance to strength training from young ages respecting physiological processes of development.